ANALISIS AKUNTANSI TABUNGAN MUDHARABAH BERDASARKAN PSAK 105 DI PERBANKAN SYARI’AH - Janillah Adha; Puja Ayu Sari; Jeki Agustiawan (UM. Bengkulu, 2025)
One of the primary fund-raising instruments in Islamic banking is mudharabah savings, which use a profit-sharing arrangement between the fund manager (mudharib) and the fund owner (shahibul maal). To guarantee accountability and transparency in financial reporting, accounting procedures that adhere to applicable accounting standards and sharia principles must be used. The purpose of this study is to examine how Islamic banks handle mudharabah savings using Statement of Financial Accounting Standards (PSAK) 105. PSAK 105, pertinent books, and scholarly journals were reviewed as part of the qualitative research technique. The findings demonstrate that, generally speaking, Islamic banks' accounting handling of mudharabah deposits has complied with PSAK 105, especially when it comes to the recognition, measurement, and presentation of mudharabah funds as temporary syirkah funds. To fully adhere to Islamic accounting standards, there are still variations in profit-sharing calculation techniques in practice, which call for more open disclosure. As a result, it is anticipated that regular application of PSAK 105 will enhance financial statement quality and boost public confidence in Islamic banking. Keywords: Mudharabah Savings, PSAK 105, Sharia Accounting, Islamic Banking.